Theatre-based social-emotional learning program to foster friendship quality in elementary school students - Fahmi Zakaria; Ninik Setyowati; Tutut Chusniyah (Research and Development in Education (RaDEn), 2024)
This research focuses on the importance of friendship quality in children's social and emotional  development, with a particular focus on primary school-aged children. The purpose of this study is to address the problem by developing a theatre-based learning module with the aim to improve friendship quality among primary school students as well as to determine the effectiveness of the module in improving friendship quality. This research methodology uses a research and development approach using the ADDIE model design. The results showed the study validated the module, achieving a high validity score of 89.94%. The Paired Samples Test revealed a significant improvement in friendship quality, with a mean score increase of -7.815 and a t-value of -3.036 (df = 26, p < 0.05). then it can be stated if the theatre-based SEL based theater programme had a significant impact on students' friendship quality. Theatre-based SEL programmes can facilitate students' understanding of emotions, enhance their ability to empathise, and encourage the development of stronger relationships. Therefore, the theatre-based module proved to be an effective approach in improving students' friendship quality.